A Work study on carparts manufacturing company - Hernandez, Christina; Hontanosas, Carlos Raymund; Tulao, Joselito (Diliman, Quezon City College of Engineering, 1992)
The main objective of this project is to help the members of the study team enhance their knowledge in Methods Engineering. Techniques of Methods Engineering are applied in the study as deemed necessary by the members. In relation to this, the team presents a documentation of the existing production system and the other systems essential to the production of the EE-90, the exhaust system manufactured by CarParts Manufacturing (CPM) Inc. In addition, it presents an analysis of current problem as well as potential problems relevant to the model under study as well as the factors affecting it. Lastly, the study team gives recommendations to solve these problems by selecting the best course of action from a list of analyzed alternatives. Various charts and diagrams such as the two handed process charts, flow process charts, and layout diagrams were used to support the facts presented in the documentation as well as in the team's analysis of the feasibility of the alternative courses of actions that can be employed to solve the problems. Illustrations, mainly on the muffler and it's parts are also included. Samples of the forms used within the present system are included. Most of the information the team has gathered were based on personal interviews conducted with our contact person, Mr. Ronnie Faygal, the company's Manufacturing Engineer. Some of the data, however, like the existing time standards were from the company's files. The charts, diagrams, and the rest of the data were based mainly on the team's observations during the plant visits. The greatest difficulty encountered by the team in conducting the study was that the team had a limited time to visit the site. The visits did not always coincide with the production schedule of the specified model. Thus, the team was unable to observe all processes involved in the manufacturing of the muffler. The study found that some of the core problems were caused by factors that are uncontrollable. Such factors as excessive product variety, poor quality of tubes, and the worker's lack of skill and experience are beyond the control of the study. There are however, core problems that are controllable. These problems are given emphasized during our study. The symptoms caused by the problems of industrial hazards, poor forms designs, layout, poor transportation and storage system, and a bottleneck department are excessive idle time in both workers and machines, and delays in deliveries as well as forced overtimes. The problems mentioned above were analyzed and the following recommendations were made : 1. Implement a formal coding system in the forms of the plant. 2. Integrate the In-plant Transfer Ticket and the Rejection Form. 3. Implement the use of metal cases as temporary storage equipment and use a specialized cart as transportations equipments. 4. Improve Safety Measures. 5. Provide Helpers to the Welders in the Welding/Assembly Department as well an incentive plant to encourage the welders to increase their output. 6. Rearrange the layout of a portion of the Pre-fabrication Department to minimize travel time and distance. Most of these recommendations involve little or no cost at all. Costs are only involved in the recommendations of metal cases and specialized carts, and the rearranging of Pre-fab layout. For the metal cases and specialized carts the costs is estimated to be between P30,000 to P40,000. For the rearrangement of layout, costs are estimated between P5,000 to P7,000. The benefits of these recommendations are measured mostly on the qualitative basis and not on a quantitative basis.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Carparts Manufacturing Incorporated; Automobile industry and trade; Systems analysis